SCIENTIFIC AND PEDAGOGICAL BASES OF THE INTEGRATED APPROACH IN THE EDUCATIONAL SYSTEM OF FOREIGN COUNTRIES DEVELOPED IN THE GLOBAL ENVIRONMENT - Turumbetova Zamira Yusupbaevna (Journals Park Publishing, 2022)
In recent years, the processes of globalization have been creating pressing and acute problems covering all fronts and spheres of human life and activity. Under the banner of globalism, serious efforts are being made to redistribute the world.
Keywords: globalization; world community; internal policy